Pengaruh Media Pembelajaran Wordwall terhadap Kemampuan Menulis Teks Fantasi Siswa Kelas VII SMP Ma’arif Gamping - Yusuf Putra Sholihin; Susetyo, Susetyo (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The use of learning media at SMP Ma'arif Gamping Sleman Yogyakarta is still less varied. Indonesian Language teachers more often use conventional learning media so that students are less active and less interested in the learning materials presented. This affects student learning outcomes in Indonesian Language Subjects. The purpose of this study was to determine and describe the effect of wordwall learning media on student learning outcomes in the material of writing fantasy texts. The research method used was a quasi-experimental method. Sampling used a purposive sampling technique involving 46 7th grade students from SMP Ma'arif Gamping. Students were divided into classes, namely the experimental class, namely class 7A, with 23 students and the control class, namely class 7B, with 23 students. The results showed that there was an increase in student learning outcomes as seen from the average posttest score of the experimental class getting a score of 80.43, while the control class score got 74.45. For the results of the hypothesis test using the t-test using the SPSS program, there is a Sig (2-tailed) result of 0.004 which shows Sig (2-tailed) < a (0.05). The results of the hypothesis test (t-test) can be concluded that there is an influence of the use of wordwall learning media on the results of learning to write fantasy texts.